2014
DOI: 10.1186/1471-2407-14-36
|View full text |Cite
|
Sign up to set email alerts
|

PMA synergistically enhances apicularen A-induced cytotoxicity by disrupting microtubule networks in HeLa cells

Abstract: BackgroundCombination therapy is key to improving cancer treatment efficacy. Phorbol 12-myristate 13-acetate (PMA), a well-known PKC activator, increases the cytotoxicity of several anticancer drugs. Apicularen A induces cytotoxicity in tumor cells through disrupting microtubule networks by tubulin down-regulation. In this study, we examined whether PMA increases apicularen A-induced cytotoxicity in HeLa cells.MethodsCell viability was examined by thiazolyl blue tetrazolium (MTT) assays. To investigate apoptot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 45 publications
(48 reference statements)
0
4
1
Order By: Relevance
“…In the current study, PMA increased cell population in S phase and decreased Sub G1 phase of the cell cycle by combining with DOX which may be the reason for the observed decrease in DOXinduced cell death in A549 cells (as the another NSCLC cell line). However, this is in contrast to few others where they have shown synergistic effects between PMA and anticancer agents in the induction of cytotoxicity accompanied by an increase in apoptotic sub-G1population [35].…”
Section: Drug Combinationcontrasting
confidence: 91%
See 1 more Smart Citation
“…In the current study, PMA increased cell population in S phase and decreased Sub G1 phase of the cell cycle by combining with DOX which may be the reason for the observed decrease in DOXinduced cell death in A549 cells (as the another NSCLC cell line). However, this is in contrast to few others where they have shown synergistic effects between PMA and anticancer agents in the induction of cytotoxicity accompanied by an increase in apoptotic sub-G1population [35].…”
Section: Drug Combinationcontrasting
confidence: 91%
“…A large body of evidence has indicated that PMA can exhibit either proliferative or anti-proliferative effects via the differential ability of protein kinase C (PKC) isoforms in regulation of the cell cycle [34]. Stimulation of PKC by PMA, can alter anticancer drug effect depending on the type of chemotherapeutic agent, phase of the cells in cell cycle at the time of activation, the specific PKC isoforms activated, and the type of cell lines [35,36]. Exposure of a panel of human NSCLC cells (e. g. H358, H441 and H322 cells) to PMA has been shown to cause distinctive responses of the cells for arrest or progression into the different phase of the cell cycle depending on which phase in the cell cycle and/or which PKC isoforms becomes activated [34].…”
Section: Drug Combinationmentioning
confidence: 99%
“…Importantly, exposure to PMA can also trigger non-ETotic cell death pathways 60 , raising the possibility that the extracellular DNA we observed was a result of cell rupture and release of DNA secondary to cell death. To distinguish between these possible scenarios, we used a combination of two DNA dyes: Hoechst, which is a membrane-permeable dye that labels DNA in both live cells and dead cells, and SytoxGreen, a non-permeable cell stain that selectively labels DNA in cells with compromised cell membranes, as observed in cells undergoing cell death (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…Importantly, exposure to PMA can also trigger non-ETotic cell death pathways 58 , raising the possibility that the extracellular DNA we observed was a result of cell rupture and release of DNA secondary to cell death. To distinguish between these possible scenarios, we used a combination of two DNA dyes: Hoechst, which is a membrane-permeable dye that labels DNA in both live cells and dead cells, and SytoxGreen, a non-permeable cell stain that selectively labels DNA in cells with compromised cell membranes, as observed in cells undergoing cell death ( Fig.…”
Section: Resultsmentioning
confidence: 96%